2020
DOI: 10.1080/02692171.2020.1815665
|View full text |Cite
|
Sign up to set email alerts
|

Global value chains – a ladder for development?

Abstract: For countries of the Global South, global value chains offer an opportunity to integrate into international trade and to industrialise relatively easily. However, in this contribution, we argue that this is not sufficient for a catching-up development, i.e. to reach the GDP per capita levels of the countries of the Global North. On the contrary, there is a risk that countries will remain trapped in low value-added activities. The theoretical argument is supported by case studies of four industries in six count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This hypothetical simultaneity bias causes endogeneity. Another simultaneity bias may arise with economic growth and labour, since GVC participation could affect economic growth (Ignatenko, Raei, and Mircheva 2019) as well as labour (Pan 2020;Dünhaupt and Herr 2021). (3) The model is built from extant literature that is not exhaustive in terms of the explanatory variables of GVCs.…”
Section: Estimation Strategymentioning
confidence: 99%
“…This hypothetical simultaneity bias causes endogeneity. Another simultaneity bias may arise with economic growth and labour, since GVC participation could affect economic growth (Ignatenko, Raei, and Mircheva 2019) as well as labour (Pan 2020;Dünhaupt and Herr 2021). (3) The model is built from extant literature that is not exhaustive in terms of the explanatory variables of GVCs.…”
Section: Estimation Strategymentioning
confidence: 99%
“…However, different paths have been identified in the existing literature (Carballa Smichowski et al, 2021), which has found that the magnitude of the benefits differs depending on the context in which the GVCs are developed, particularly with respect to the firms' ownership within the GVC. Thus, while Asian State‐owned firms become national champions, in Latin America private companies do not provide benefits for the host country (Dünhaupt & Herr, 2021; Ravenhill, 2014). Additionally, offshoring strategies implemented by firms located in developed countries allow the creation of new jobs (SDG 8), often also for women due to their specific skills which are needed for production activities (SDG 5).…”
Section: Impacts Of Backshoring Strategies On Sdgs In Home and Host C...mentioning
confidence: 99%
“…Davis and Caldeira ( 2010 ) argue that a consumption-based accounting of CO 2 emissions indicates the potential for global carbon leakage, with the majority of international trade in CO 2 emissions coming from China and other developing markets and being exported to consumers in industrialized countries. Furthermore, Dünhaupt and Herr ( 2021 ) all considered the fact that the majority of developing countries, like China, join GVCs by exporting comparatively large amounts of finished goods in their early stages of development, which generates a significant amount of CO 2 emissions and forces the poorer nations to bear the costs of natural depletion.…”
Section: Literature Reviewmentioning
confidence: 99%